The potential for circular dichroism as an additional facile and sensitive method of monitoring low-molecular-weight heparins and heparinoids - Rudd, Timothy R.; Skidmore, Mark A.; Guimond, Scott E.; Holman, Joseph; Turnbull, Jeremy E.; Lauder, Robert M.; Fernig, David G.; Yates, Edwin A. (Thrombosis and Haemostasis, 2009)
The ultraviolet circular dichroism (CD) spectra of commercial low-molecular-weight heparins, heparinoids and other anticoagulant preparations have been recorded between 180 and 260 nm. Principal component analysis of the spectra allowed their differentiation into a number of groups related to the means of their production reflecting the structural changes introduced by each process. The findings suggest that CD provides a complementary technique for the rapid analysis of heparin preparations.
Keywords: Circular dichroism; low-molecular-weight heparin; heparinoids; principal component analysis; quality control